Three dimensional visualization of semiconductor multi-quantum well interfaces - Mackenzie, R; Cerezo, A; Grovenor, C (Publ by IOP Publishing Ltd, 1991)
Individual interfaces in multiquantum well materials have been imaged in three dimensions using the position sensitive atom probe. The location and chemical identity of single atoms within a small volume have been determined and a constant composition contour constructed in three dimensions. This form of observation makes it possible to directly assess the interface morphology.